2017
DOI: 10.1371/journal.pone.0183280
|View full text |Cite
|
Sign up to set email alerts
|

HIV self-testing values and preferences among sex workers, fishermen, and mainland community members in Rakai, Uganda: A qualitative study

Abstract: HIV self-testing may encourage greater uptake of testing, particularly among key populations and other high-risk groups, but local community perceptions will influence test uptake and use. We conducted 33 in-depth interviews and 6 focus group discussions with healthcare providers and community members in high-risk fishing communities (including sex workers and fishermen) and lower-risk mainland communities in rural Uganda to evaluate values and preferences around HIV self-testing. While most participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 33 publications
6
50
2
Order By: Relevance
“…Sex work criminalization in Kenya, Zimbabwe, Uganda and South Africa, Canada, Uzbekistan and Russia [24, 25, 27, 32, 51, 52, 54] and fear of registration as a drug-user in Russia [24, 34] are seen to have hampered access to healthcare, including testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex work criminalization in Kenya, Zimbabwe, Uganda and South Africa, Canada, Uzbekistan and Russia [24, 25, 27, 32, 51, 52, 54] and fear of registration as a drug-user in Russia [24, 34] are seen to have hampered access to healthcare, including testing.…”
Section: Resultsmentioning
confidence: 99%
“…In one study examining hypothetical circumstances around self-testing, participants reported to anticipate significant benefits (entire privacy, avoiding travel and time costs, ability to test before sex early diagnosis), although these same features raised concerns when associated with lack of supportive counseling and linkage to care [54]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Malawi, Tanzania, Uganda, and South Africa also supported the importance of pre-and post-HIV counselling for men to ensure that men are not left isolated [11,12,26,28,29,31,35]. The pre-HIVST counselling would likely assess men's readiness to respond to a potential HIV positive test outcome [32].…”
Section: Need For Hivst Counsellingmentioning
confidence: 99%
“…As a result of the research method used (qualitative or mixed methods), qualitative data from the sixteen included studies were extracted. The included studies were conducted in the following countries: Zambia [24], Malawi [11,25], South Africa [12,[26][27][28][29][30], Tanzania [31][32][33], Uganda [34,35], Zimbabwe and Malawi [36], and Kenya [37]. Twelve studies were predominantly qualitative and four were mixed methods.…”
Section: The Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation